DOMINANSI SPESIES TUMBUHAN INVASIF PADA KOMUNITAS TUMBUHAN DI KEBUN RAYA TANJUNG PURI TABALONG, KALIMANTAN SELATAN - Erni Widiyawati; Gusti Muhammad Hatta; Yudi Firmanul Arifin; Basir Basir (Universitas Lambung Mangkurat, 2022)
The presence of potentially invasive plant species in the midst of native South Kalimantan pamah plants can inadvertently be carried away by tourists and several types of fauna such as birds and squirrels. This study aims to analyze the diversity of invasive plant species, and their dominance in the plant community in Tanjung Puri Tabalong Botanical Gardens, South Kalimantan. This research was conducted at the Tanjung Puri Botanical Gardens which is administratively located in Kasiau Village, Murung Pudak District. Points A.1 and A.2; measuring plots on rubber plantation vegetation, Points B.1 and B.2; measuring plots on shrubby vegetation – grasslands and Points C.1 and C.2; plots of forest vegetation. Plant Composition (Important Value Index) The formula or equation to calculate the INP. The plant species identified in Tanjung Puri Tabalong Botanical Gardens were 57 species from 32 families. There were 5 species from 5 invasive plant families with the highest importance index and dominance index found at the three research sites, namely Acacia mangium, Vitex pinnata L, Eupatorium inulifolium, Imperata cylindrica, and Melastoma malabathricum.